Uji Daya Hambat Ekstrak Teh Hijau (Camellia sinensis) Terhadap Pertumbuhan Candida albicans Secara In Vitro - Chaidir Ali Paradise; Dian Ayu Fitriani; Rolly Riksanto Bahtiar (Jurnal MedScientiae, 2023)
Candidiasis is any  infection  caused by Candida albicans and other species of the genus Candida. Bioactive compounds such as flavonoid, tannin and saponin have antifungal activity. Several studies have investigated the bioactive compounds  in green tea leaves (Camellia sinensis). Objective is to determine the ability of  green tea leaf extract (Camellia sinensis) to combat the growth of Candida albicans. A true experimental study. Green tea leaf (Camellia sinensis) and Candida albicans extract were used as the sample. Results According to the Davis and Stout method, green tea (Camellia sinensis) extracts at concentrations of 25% and 75% showed moderate inhibition of Candida albicans growth on the first day of  Candida albicans incubation. , while 50% concentration showed strong inhibition. against the growth of Candida albicans and on the second day at concentrations of 25%, 50% and 75%  the growth of Candida albicans was not prevented. While the positive control using nystatin strongly inhibited and the negative control did not inhibit the growth of Candida albicans on the second day. first and second. Green tea leaf (Camellia sinensis) extract effectively inhibits the growth of Candida albicans during incubation.